Development of Learning Media for Ubrug Traditional Theater Documentary Films for Class X Students at Senior High School 8 Serang City - Dimyati, Ahmad; Roekmana, Giri Mustika; Septiyan, Dadang Dwi (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
This study aims to find out how the development and feasibility of Ubrug Traditional Theater Documentary Film learning media is motivated by the problems found at Senior High School 8 Kota Serang. This study uses research and development (R&D) research methods with the ADDIE research model which has five stages, namely analyze, design, development, implementation, and evaluation. Data collection techniques used were observation, interviews, and questionnaires. The data analysis technique uses descriptive quantitative analysis techniques. The results of this study indicate that the learning media for Ubrug Traditional Theater Documentary Film